CORRELATION BETWEEN AGE, EDUCATION, PARITY, SOCIAL SUPPORT, AND THE INCIDENCE OF POSTPARTUM BLUES - Ika Novita Sari; Tukimin Bin Sansuwito (Yayasan Media Utama Sains, 2024)
Background: Postpartum Blues is a psychological condition that occurs in mothers after childbirth. In Indonesia, the prevalence of Postpartum Blues is 1 to 2 per 1000 births. As many as 53% of postpartum mothers experience symptoms such as mood swings and difficulty regulating emotions for no apparent reason, which is an indication of Postpartum Blues syndrome. Objective: This study aims to determine the factors associated with the occurrence of Postpartum Blues syndrome in mothers after childbirth. Methods: This study used a quantitative approach using a cross-sectional strategy. This study involved a sample of 30 postpartum mothers selected by the Accidental Sampling technique. The data collection process was carried out using a questionnaire. This study used the Chi-Square test. Results: The results showed that in PMB X Batam City, the majority of postpartum mothers were adults (56.6%), had several previous pregnancies (56.7%), had completed high school education (46.6%), and did not receive social support (53.3%). The results showed that there was a significant relationship between age, parity, education, and social support with the occurrence of Postpartum Blues in postpartum mothers (p=0.003, p=0.024, p=0.441, p=0.282, and p=0.011). Conclusion: The incidence of Postpartum Blues in postpartum mothers is influenced by age, parity, and social support. However, there is no relationship between education level and the incidence of Postpartum Blues.